Effects of autologous platelet transfusion on platelet inhibition in ticagrelor‐treated and clopidogrel‐treated subjects - Teng, R.; Carlson, G. F.; Nylander, S.; Andersson, T. L. G. (Journal of thrombosis and haemostasis, 2016)
Essentials Limited data on hemostatic benefits of platelet transfusion (PT) exist. 44 healthy subjects had a single dose of ticagrelor or clopidogrel ± autologous PT post‐dosing. PT did not reverse ticagrelor's antiplatelet effects and had minimal impact post clopidogrel. Post‐ticagrelor, PT is unlikely to be beneficial, and the benefits post‐clopidogrel are unknown. Summary Background Antiplatelet agents increase bleeding risk. Few data on hemostatic benefits of platelet transfusion exist. Objective To assess the effect of autologous platelet transfusion on ticagrelor‐mediated and clopidogrel‐mediated platelet inhibition in a single‐center, open‐label, randomized, cross‐over study (NCT01744288). Methods Forty‐four healthy subjects received ticagrelor (180 mg) or clopidogrel (600 mg; two functional CYP2C19 alleles [*1 or *17] required) with or without platelet transfusion (14‐day washout). Subjects received one autologous platelet apheresis unit (approximately six pooled donor platelet units) 24 h (n = 15) or 48 h (n = 13) after ticagrelor or 48 h after clopidogrel (n = 16). Platelet apheresis was conducted 72 h before transfusion. Aspirin (81 mg per day) was taken from after apheresis until 24 h before transfusion. P2Y12 reaction units (PRUs) and inhibition of platelet aggregation (IPA) induced by ADP were measured. Results Mean age and body mass index were 30 years (standard deviation [SD] 6 years) and 26.9 kg m−2 (SD 4.0 kg m−2), respectively; 98% of subjects were men, and 39 of 44 completed treatment. Platelet transfusion 24 h after ticagrelor had minimal effects on IPA or PRU values within 48 h after transfusion. Platelet transfusion 48 h after ticagrelor also had minimal effects on IPA or PRU values at most post‐transfusion times. Platelet transfusion 48 h after clopidogrel, versus no transfusion, had a small reversing effect on IPA (24 h, 36 h, and 48 h) and PRU values (12 h, 24 h, and 36 h) after transfusion. Conclusions Autologous platelet transfusion is unlikely to be of clinical benefit in reversing the antiplatelet effects of ticagrelor. The clinical relevance of the small effects seen with clopidogrel is unknown.